(untitled) (Canadian Dermatology Today, 2022)
Deoxycholic acid is a secondary bile acid that aids in the emulsification of fat for absorption in the intestine. In 2015, Health Canada approved non-animal, non-human, synthetically derived deoxycholic acid (DCA injection: ATX-101; KYBELLA, Madison, New Jersey; BELKYRA, Canada and Sweden; KYTHERA Biopharmaceuticals, Inc., Westlake Village, CA, acquired by Allergan, Inc.) for the treatment of moderate-to-severe submental fat. Available in a 2 mL vial of 10 mg/mL solution, deoxycholic acid is injected into affected areas at 0.2cc per cm. Deoxycholic acid causes adipocytolysis one to three days after being injected directly into adipose tissue by irreversibly disrupting the adipocyte cell membrane. One week after injection, macrophages are recruited to the area, and by day 28 fibroblasts and evidence of neocollagenesis can be seen, resulting in lasting fat reduction within the treated area.